Analysis of Management Efficiency and Financial Performance in Supporting the Consistency of the Top Brand Index (TBI) of PT Campina Ice Cream Industry Tbk for 2019-2024: Analisis Efisiensi Manajemen dan Kinerja Keuangan dalam Mendukung Konsistensi Top Brand Index (TBI) PT Campina Ice Cream Industry Tbk Tahun 2019–2024 - Aurelia Shafarina Firdausi (Business Finence Analyst Co.,, 2025)
This study analyzes the role of management efficiency and financial performance in supporting the consistency of the Top Brand Index (TBI) of PT Campina Ice Cream Industry Tbk during the 2019–2024 period. The research adopts a quantitative longitudinal case study approach using secondary data obtained from the company’s annual financial reports and official Top Brand Index publications. Management efficiency is measured through an Efficiency Index derived from Total Assets Turnover (TATO) and Inventory Turnover, while financial performance is measured using a Financial Index constructed from Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Advertising-to-Sales Ratio. Data analysis includes descriptive statistics, Shapiro–Wilk normality tests, Spearman correlation analysis, and exploratory multiple linear regression. These findings suggest that the consistency of the Top Brand Index is not directly driven by internal financial performance or operational efficiency alone, but is more likely influenced by intangible factors such as consumer perception, brand experience, and long-term brand equity. This study highlights the indirect relationship between financial performance and brand strength in the fast-moving consumer goods industry.